Feasibility and Accuracy of Pedicle Screws in the Feline Thoracolumbar Spine - Rigo, Matteo; Cinti, Filippo; Menchetti, Marika; Ventura, Laura; Pratesi, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
To evaluate the feasibility and accuracy of vertebral pedicle screws in cats using a custom 3D-printed drill guide and 3D-printed vertebral columns.To simulate the surgical procedure, six vertebral columns from adult cats were 3D-printed. The columns were printed with a radiolucent material (PLA enriched with calcium carbonate—PLA+). One 3D-printed guide was created for each vertebra (from T10 to L7). Each preplanned hole was drilled and filled with a graphite cylinder for better visualization of the tunnel. All the phantoms were CT-scanned after the drilling operation. Each hole was graded using a modified classification scheme (grades 0 to 3) and compared to the planned tunnel angle. We enrolled one 5-year-old female patient with spinal trauma requiring vertebral stabilization presented at our hospital.A total of 126 holes were drilled. The overall mean screw deviation angle was 0.61 degrees (SD = 0.72). In safety evaluation, 117 (93%) screws were contained in the pedicle (grade 0), 7 screws (5.5%) were outside the pedicle by less than 0.5 mm (grade 1), and 2 (1.5%) screws were between 0.5 and 1 mm outside the pedicle. In the thoracic segment, all the holes (48/48) were classified as a grade 0, while in the lumbar segment, with a total of 78 holes drilled, there were 69 holes classified as grade 0 (88%), 7 holes classified as grade 1 (8.9%), and 2 holes classified as grade 2 (2.5%). The feline patient had suffered a T12 complete oblique vertebral body fracture. A total of six 1.7 mm screws, 20 mm long, (Fix-In, INTRAUMA) were placed: three in T12 and three in T13.Overall, there was a mean deviation of the hole angle from the planned angle of 0.61 degrees. The overall safety was 91.2% (screws graded as 0). A statistically significant association between screw grades and vertebral segment was found (p-value 0.02) as all the thoracic vertebrae are grade 0, while grade 1 and grade 2 were found only in the lumbar segment. Using pedicle screws in cats' vertebrae may reduce surgical trauma, as it requires exposure of only the most dorsal portion of the vertebral lamina, avoiding the need to expose the costal attachments. Also, placing cement dorsally is easier and can incorporate screw heads bilaterally. We effectively and safely performed the surgical procedure in one clinical case. Based on our results, the use of pedicle screws, previously applied in canine patients, could also be extended to feline patients, provided that 3D-printed guides are used to ensure accurate placement.
Keywords: bioengineering; fracture repair; orthopaedic devices; spine surgery